2015
DOI: 10.1080/08870446.2015.1050393
|View full text |Cite
|
Sign up to set email alerts
|

Effect of an intervention mapping approach to promote the consumption of fruits and vegetables among young adults in junior college: A quasi-experimental study

Abstract: These results may be used to guide health promoters working with college students.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 38 publications
1
7
0
1
Order By: Relevance
“…Less than half of the students consider plant sources, nutrient value, or follow a healthy diet when they choose food. These results agree with the findings of several studies [32][33][34][35].…”
Section: Discussionsupporting
confidence: 93%
“…Less than half of the students consider plant sources, nutrient value, or follow a healthy diet when they choose food. These results agree with the findings of several studies [32][33][34][35].…”
Section: Discussionsupporting
confidence: 93%
“…The researchers found that the intervention increased the number of college students eating at least five servings of fruits and vegetables. They emphasized the importance of developing interventions tailored to college students to promote healthy behaviors [8].…”
Section: Health Promotion and Healthy Behaviorsmentioning
confidence: 99%
“…Some researchers have investigated various ways to promote the consumption of fruits and vegetables among students, and their interventions showed positive results [34,35], especially when combining educational aspects with environmental ones [36].…”
Section: Introductionmentioning
confidence: 99%